Disparities Among Pediatric Firearm Suicides in the United States: An Analysis of the National Violent Death Reporting System, 2014 to 2018 - DiVietro, Susan (Journal of interpersonal violence, 2024)
Suicide is a leading cause of death in the United States (U.S.), with firearms being the predominant method. This study examines the racial disparity and disproportionality of pediatric firearm suicide from 2014 to 2018 in 17 U.S. states. We used the National Violent Death Reporting System to quantify the burden of pediatric firearm suicide by race/ethnicity and gender and assessed themes among decedents aged 10 to 17 years. Racial disparity and disproportionality were measured using the Disparity Index and Disproportionality Representation Index, respectively. Decedents were primarily non-Hispanic White (NHW, 77.5%) and male (84.0%). NHW children died at a rate that was 1.3 times greater than expected based on their proportion in the general population and were 2.6 times more likely to die by firearm suicide than non-Hispanic Black (NHB) children. NHB children were less likely to disclose suicide intention, suggesting that this group may require more active screening intervention. Qualitative analysis revealed unsafe firearm storage as a common theme among these deaths. Differences in age with respect to social media use and precipitating factors such as bullying and arguments with parents were also identified as contributing factors. Results of this study support the expansion of interventions such as lethal means restriction counseling and implementation of safer firearm storage laws.